Optimal Central Bank Conservatism and Monopoly Trade Unions - Hefeker, Carsten (IMF Working Papers; Working Paper, 2002)
The "conservative central banker" has come under attack recently. On the basis of models in which there is explicit interaction between trade union behavior and monetary policy, it has been argued that if 'trade unions' are averse to inflation, welfare will be lower with a conservative than with a liberal central bank. We reframe this discussion in a standard trade union model. We show that the case against the conservative central banker rests exclusively on the assumption of a strictly nominal outside option (for instance, unemployment benefits) for the union. There is no welfare gain associated with making the central bank less conservative than society, however, if the outside option is in real terms. As the nominal components of the trade union's outside option are mainly public transfers, we also show that the conservative central banker is always optimal if the government can choose the level of nominal unemployment benefits as well as the degree of central bank conservatism.